2017
DOI: 10.1007/978-3-319-57193-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease: Pathogenic Mechanisms and Therapeutic Targets

Abstract: Huntington's disease (HD) is a tandem repeat disorder involving neurodegeneration and a complex combination of symptoms. These include psychiatric symptoms, cognitive deficits culminating in dementia, and the movement disorder epitomised by motor signs such as chorea. HD is caused by a CAG repeat expansion encoding an extended tract of the amino acid glutamine in the huntingtin protein. This polyglutamine expansion appears to induce a 'change of function', possibly a 'gain of function', in the huntingtin prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 220 publications
1
10
1
Order By: Relevance
“…Huntington disease (HD) is a rare genetic autosomal dominant neurodegenerative syndrome triggered by expanded CAG repeats in the huntingtin gene, which leads to pathological elongation of huntingtin with a polyglutamine tract. The neurodegenerative conditions caused due to HD lead to cognitive, motor, and psychiatric symptoms, atrophy of the basal ganglia and the cerebral cortex (Wright et al, 2017;Illarioshkin et al, 2018). Transcriptional dysregulation has been suggested a prominent mechanism for pathogenesis of HD (Sharma and Taliyan, 2015b).…”
Section: Huntington Diseasementioning
confidence: 99%
“…Huntington disease (HD) is a rare genetic autosomal dominant neurodegenerative syndrome triggered by expanded CAG repeats in the huntingtin gene, which leads to pathological elongation of huntingtin with a polyglutamine tract. The neurodegenerative conditions caused due to HD lead to cognitive, motor, and psychiatric symptoms, atrophy of the basal ganglia and the cerebral cortex (Wright et al, 2017;Illarioshkin et al, 2018). Transcriptional dysregulation has been suggested a prominent mechanism for pathogenesis of HD (Sharma and Taliyan, 2015b).…”
Section: Huntington Diseasementioning
confidence: 99%
“…HD is a genetic disorder characterized by movement disorder, cognitive decline, and behavioral difficulties (Walker, 2007; Wright et al, 2017; Pandey and Rajamma, 2018). As found in post-mortem and MRI studies, HD patients suffer from neuronal cell death, initially and mostly in the striatum but also in the cortex and other areas of the brain (Reiner et al, 1988; Rosas et al, 2003).…”
Section: Er Stress and Huntington's Diseasementioning
confidence: 99%
“…There is currently no cure or effective therapy for HD. There are two main recent experimental approaches to try to develop a therapy (reviewed in Huang et al, 2016; Wright et al, 2017; Caron et al, 2018; Saavedra et al, 2018). One involves gene therapy, which includes knockdown of mHtt (Aguiar et al, 2017; Datson et al, 2017; Southwell et al, 2018) and expression of miRNAs (Miniarikova et al, 2017; Evers et al, 2018) (Table 1).…”
Section: Therapeutic Approaches For Hdmentioning
confidence: 99%
“…When processing information, the brain exploits various components to help encode the information and categorize the information into longterm memory. Magnetic resonance imaging (fMRI) data indicates that long-term memory, such as episodic memory and item memory, is active in the hippocampus (Scott, 2017;Wright, Renoir, Gray, & Hannan, 2017). Mergel (1998) showed that long-term memory has an unrestricted capacity.…”
Section: Cognitive Process In Human Memory Systemmentioning
confidence: 99%